2003
DOI: 10.1007/s00299-003-0623-8
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Thapsia garganica—a medicinal plant

Abstract: The micropropagation of T. garganica, a medicinally important plant, was investigated as an option for conservation purposes as wild populations are becoming sparse. A Murashige and Skoog agar medium supplemented with 0.5 mg l(-1) alpha-naphthaleneacetic acid and 1.5 mg l(-1) benzyl-6-adenine significantly improved the production of multiple shoots directly from petiole and leaflet explants compared to other plant growth regulator (PGR) combinations. Medium free of PGRs promoted rooting at a low incidence. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 13 publications
6
41
1
Order By: Relevance
“…The produced plantlets could be directly acclimatized without passing through a rooting phase. Likewise, shoot production and rooting in one-phase was also observed for Thapsia garganica (Makunga et al 2003), Pinguicula lusitanica (Gonçalves et al 2008) and Crithmum maritimum (Grigoriadou and Maloupa 2008).…”
supporting
confidence: 54%
“…The produced plantlets could be directly acclimatized without passing through a rooting phase. Likewise, shoot production and rooting in one-phase was also observed for Thapsia garganica (Makunga et al 2003), Pinguicula lusitanica (Gonçalves et al 2008) and Crithmum maritimum (Grigoriadou and Maloupa 2008).…”
supporting
confidence: 54%
“…Shoot proliferation decreased significantly under higher concentrations of BA, or when no IAA was present. Higher concentrations of BA (whether applied alone, or in combination with auxin) are known to decrease the number of new microshoots per explant in other for 12 months Apiaceae such as Thapsia garganica (Makunga et al 2003), E. foetidum (Gayatri et al 2006), Crithmum maritimum (Grigoriadou and Maloupa 2008), Arracacia xanthorrhiza (Sliva et al 2010), and Anethum graveolens (Jana and Shekhawat 2012). In contrast, the efficiency of shoot proliferation in Centella asiatica, and Vanasushava pedata was seen to increase in concentrations of up to 5.0 mg L -1 BA (Tiwari et al 2000;Karuppusamy et al 2006).…”
Section: Shoot Induction and Proliferationmentioning
confidence: 99%
“…Root development with an intermediary callus indicated that at that roots and shoots were not well connected with vascular tissue and that plants are insuffi ciently supplied with nutrients (George 1993). Successful rooting in other members of the Apiaceae family was also achieved with 1-5 μM IBA (Tavares et al 2010a, Das et al 2008, Jana and Shekhawat 2011, Coste et al 2012, Jaheduzzaman et al 2012, and with higher concentrations of IBA (Hossain et al 2000, Sharma and Wakhlu 2001, Banerjee et al 1999, Tavares et al 2009-2010, with NAA or IAA (Karuppusamy et al 2007, Jaheduzzaman et al 2012) and only rarely without growth regulators (Makunga et al 2003).…”
Section: Root Initiationmentioning
confidence: 99%
“…The seeds in our experimental system germinated only after cold treatment and did not germinate at all in growth chamber conditions. The reason for this late and low germination could be dormancy, which is not unusual for seeds of the Apiaceae family (Hendrawati et al 2012, Baskin andBaskin 2014), or possible loss of viability (Makunga et al 2003, Mondoni et al 2011. Sterilization only slowed the rate of early germination and slightly infl uences the fi nal germination of cold treated seeds.…”
Section: In Vitro Seed Germination and Initiation Of The Culturementioning
confidence: 99%